Application of 3D Printing for Smart Objects with Embedded Electronic Sensors and Systems. Issue 1 (2nd March 2016) - Ota, Hiroki; Emaminejad, Sam; Gao, Yuji; Zhao, Allan; Wu, Eric; Challa, Samyuktha; Chen, Kevin; Fahad, Hossain M.; Jha, Amit K.; Kiriya, Daisuke; Gao, Wei; Shiraki, Hiroshi; et al.
Abstract : Applications of a 3D printing process are presented. This process integrates liquid‐state printed components and interconnects with IC chips in all three dimensions, various orientations, and multiple printing layers to deliver personalized system‐level functionalities. As an example application, a form‐fitting glove is demonstrated with embedded programmable heater, temperature sensor, and the associated control electronics for thermotherapeutic treatment.